Manipulating of nanometer spacing dual-wavelength by controlling the apodized grating depth in microring resonators - Amiri, Iraj Sadegh; Zakaria, Rozalina; Yupapin, Preecha Promphan (Elsevier, 2019)
We propose a passive photonic design for an optically pumped laser system and tunable dual-wavelength generation application by employing optical nonlinear mode coupling of two coupled III–V semiconductor microring resonators, which is connected to a pump and drop waveguide buses. One of the two rings contains a grating, whereas the other has a planar surface. The mechanism underlying the dual-wavelength generation can be explained via the resonance detuning of the spectra that results in nonlinear mode mixing. The tunability of the wavelengths can be achieved by altering the grating depth of the microring resonator and the power coupling coefficients. In the grating design of the microring resonators, we have selected a trapezoidal-profiled apodized grating to obtain low reflectivity at the sidelobes. A time-domain traveling wave (TDTW) analysis yields an InGaAsP core refractive index of 3.3. This core is surrounded by a grating InP cladding with a refractive index of 3.2. We further confirm that the propagation of a Gaussian pulse input with a power of 10 mW and a bandwidth of 0.76 ps is well confined within the system mode propagation. The results show a 2:1 fan-out of two spectrally separate signals, which can be employed for compact and high functional sources on chips.